Legal Analysis of Law Enforcement of Mining Crimes Based on Legal Certainty - Pahala Holmes Hutagalung; Arpangi Arpangi (UNISSULA Semarang, 2025)
This study aims to determine and analyze the implementation of law enforcement against illegal mining crimes in law enforcement against mining crimes that have legal certainty and obstacles and solutions in law enforcement against mining crimes that have legal certainty. The method of sociological juridical approach, the research specification is descriptive analytical, the data used are primary data and secondary data. The data collection method is field study and literature study. The data analysis method used is qualitative. The theory used in this study is the theory of legal law enforcement and the theory of legal certainty. Based on the results of the study, it can be concluded that law enforcement against mining crimes in the West Kalimantan Regional Police has legal certainty where its implementation is based on applicable laws and regulations, namely the Minerba Law, the Criminal Procedure Code and the Police Chief Regulation Number 6 of 2019 concerning Criminal Investigation. The implementation of law enforcement is carried out through investigations and inquiries into events suspected of having occurred mining crimes. Obstacles in law enforcement against mining crimes include internal obstacles and external obstacles. Through appropriate solution actions, these obstacles can be overcome, so that the law enforcement process can be carried out in accordance with the provisions of applicable laws and regulations.